Asymptomatic Mycoplasma genitalium infection amongst marginalised young people accessing a youth health service in Melbourne. (March 2014) - Henning, Dorothy; Eade, Donna; Langstone, Alison; Bean-Hodges, Alison; Marceglia, Alexandra; Azzopardi, Peter
We conducted a study to establish the prevalence of Mycoplasma genitalium amongst asymptomatic young people experiencing homelessness in the context of comprehensive health care delivery. All asymptomatic young people at risk of sexually transmitted infections were offered urinary polymerase chain reaction testing for M. genitalium whilst being tested for Chlamydia trachomatis and Neisseria gonorrhoeae over a four-month period in 2012. Those who tested positive were notified of the infection and offered treatment. Sixty asymptomatic young people (36 female and 24 male) were tested for M. genitalium, identifying eight cases (13%) (six female and two male). Ten young people (17%) tested positive for C. trachomatis, three (5%) of whom were positive for both M. genitalium and C. trachomatis . There were no cases of N. gonorrhoeae . Of the eight cases of M. genitalium, seven were contactable and five were treated at our clinic with azithromycin 1 g stat. Two of the five returned after a month for a test of cure, identifying one resistant infection. Further data on the epidemiology of M. genitalium are required before testing recommendations can be made; however, consideration should be given to testing for M. genitalium in settings where other sexually transmitted infections are prevalent.